From Stages to Varieties of Capitalism: Lessons, Limits and Prospects - Özveren, Eyüp; Havuç, Utku; Karaoğuz, Emrah (Panoeconomicus, 2012)
The basic aim of this paper is to take a tour de force in order to put the varieties of capitalism (VoC) approach in perspective and to assess its limits and further prospects. There existed before it a certain stages-of-capitalism (SoC) approach with a long history. The SoC approach developed largely under the influence of social and anthropological stage theories of progress and of Marxism. Accordingly, capitalism as a mode of production was perceived as progressing through commercial, industrial, and financial stage. In this paper, this link will be recovered for the benefit of further scholarship. We emphasize that the VoC approach, by the weight it puts on efficiency tends to rank circumstantially the variety at issue, thereby implying occasionally a desirable move towards the more efficient form. This means that the elements forming a given variety may actually be matched with the successive stages of a certain progress.Key words: Varieties of capitalism, Stages of capitalism, Transition, Convergence, Institutionalism.JEL: B13, B25, N0.